DM DISEASE PREVENTION THROUGH IMPROVED KNOWLEDGE AND SKILLS OF NON-COMMUNICABLE DISEASE SCREENING AMONG HEALTH CADRES - Eliyah, Eliyah; Wijayanto, Setya; Mustofa, Ibnu Arkhan Mustofa (LPPM Univ. Ibn Khaldun Bogor, 2024)
One of the non-communicable diseases (NCDs) is diabetes mellitus (DM), which is characterised by high blood sugar levels and metabolic disorders of carbohydrates, lipids, and proteins due to insufficient insulin function. Early detection is rare due to the absence of complaints. The government, through BPJS Kesehatan, urges JKN participants aged >= 15 years to conduct health history screening with the aim of identifying potential risks for diabetes mellitus, hypertension, coronary heart disease, and chronic kidney disease. Empowerment and increased community participation through Posbindu PTM activities with its cadres are two of the efforts to control DM disease and its complications. The purpose of this community service (Pengabmas) is to provide education and training on diabetes and its complications to health cadres in Jabungan Village, Semarang City, as partners in this Pengabmas. This community service uses the Active Human Learning Method (CBIA), which consists of two activities: counselling through videos containing material on the introduction of safe carbohydrates as a prevention of diabetes mellitus and its complications, and training in the early detection skills of NCDs through BPJS web screening. This activity was attended by 16 cadres, who were very enthusiastic during the activity. The results of the activity showed an increase in cadre knowledge in the good category by 80% and sufficient knowledge by 20%.